2019
DOI: 10.1016/j.isci.2019.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling of Biliary Tract Cancer Cell Lines Reveals Molecular Subtypes and Actionable Drug Targets

Abstract: SummaryBiliary tract cancers (BTCs) currently have no approved targeted therapies. Although genomic profiling of primary BTCs has identified multiple potential drug targets, accurate models are needed for their evaluation. Genomic profiling of 22 BTC cell lines revealed they harbor similar mutational signatures, recurrently mutated genes, and genomic alterations to primary tumors. Transcriptomic profiling identified two major subtypes, enriched for epithelial and mesenchymal genes, which were also evident in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…A). This is in line with the previously described frequent MAPK signaling activation in biliary tract cancers ( 21 ) (Supporting Fig. B).…”
Section: Resultssupporting
confidence: 92%
“…A). This is in line with the previously described frequent MAPK signaling activation in biliary tract cancers ( 21 ) (Supporting Fig. B).…”
Section: Resultssupporting
confidence: 92%
“…However, due to the rarity of BTC, large-scale clinical trials are challenging to establish. Recently, it was demonstrated that BTC cell lines and organoids have genomic alterations similar to those in primary tumors, indicating that they could be useful in developing and validating therapeutic targets for BTC [ 42 ]. As shown in this study, identifying actionable genes and candidate drugs using KBs could facilitate comprehensive validation using cell lines and organoids.…”
Section: Discussionmentioning
confidence: 99%
“…The work of Akita et al [26] found that IDH1 mutation is typical in iCCA derived from small bile duct as well as the loss of BAP1; in contrast, loss of SMAD4 expression, KRAS mutations, and MDM2 amplification are mainly found in large bile duct iCCA. A very recent study has focused on the in-depth characterization of 22 CCA cell lines, including gallbladder carcinoma, by exome sequencing, copy number, and RNA-seq analyses [27]. This large panel of cell lines, which differ in their site of origin, molecular alterations, and mutational status, represents a valid tool for drug screening tests, in particular for targeted therapy (Table 1).…”
Section: D Models: Cell Lines and Primary Cell Culturesmentioning
confidence: 99%